286OPhase III KEYNOTE-048 study of first-line pembrolizumab for recurrent/metastatic head and neck squamous cell carcinoma: Asia vs non-Asia subgroup analysis. (24th November 2019) - Ngamphaiboon, N; Tanaka, K; Hong, R-L; Wan Ishak, W Z; Yen, C-J; Sriuranpong, V; Takahashi, S; Srimuninnimit, V; Yeh, S-P; Oridate, N; Yang, M-H; Nohata, N; et al.
Abstract: Background: KEYNOTE-048 (NCT02358031) is a randomized, open-label, phase 3 trial of pembrolizumab (pembro) or pembro + chemotherapy (chemo) vs EXTREME (E) as first-line therapy for recurrent and/or metastatic (R/M) head and neck squamous cell carcinoma (HNSCC). At the second interim analysis, overall survival (OS) was significantly longer with pembro than E in patients with PD-L1 combined positive score (CPS) ≥20 (P = 0.0007) and CPS ≥1 (P = 0.0086) and was noninferior in the total population (pop). Pembro + chemo significantly improved OS vs E in the total pop (P = 0.0034). Safety was favorable or similar to that of E. Methods: Patients with R/M HNSCC not curable by local therapy and with no prior systemic therapy were randomized (1:1:1) to pembro 200 mg Q3W, pembro + chemo (cisplatin 100 mg/m 2 or carboplatin AUC 5 Q3W + 5-FU 1000 mg/m 2 /day for 4 days Q3W), or E (cetuximab 400 mg/m 2 loading dose with 250 mg/m 2 subsequent infusion QW + chemo) until progressive disease, unacceptable toxicity, 6 cycles of chemo, or 24 months of pembro. Primary end points were progression-free survival and OS. Data cutoff date was June 13, 2018. Results: Efficacy is reported in the table. Gr 3-5 drug-related AE rates with pembro vs E were 28.6% vs 76.9% in the Asia subgroup and 13.9% vs 67.2% in the non-Asia subgroup; rates with pembro + chemo vs E were 71.9% vs 76.9% in the Asia subgroup and 70.8% vs 67.2% in the non-Asia subgroup. Conclusions: Pembro vs E showed favorable OS in Asia and non-Asia subgroups, regardless of PD-L1 status; responses were durable, particularly among all non-Asia subgroups; safety was favorable. Pembro + chemo vs E showed favorable OS in patients with CPS ≥20 in Asia and non-Asia subgroup regardless of PD-L1 status, durable responses, and similar safety. Clinical trial identification: NCT02358031. Editorial acknowledgement: Medical writing and/or editorial assistance was provided by Doyel Mitra, PhD, CMPP, and Holly Cappelli, PhD, CMPP, of the ApotheCom pembrolizumab team (Yardley, PA, USA). This assistance was funded by Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA. Legal entity responsible for the study: Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA. Funding: Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA. Disclosure: N. Ngamphaiboon: Honoraria (self): Roche, AstraZeneca, Eisai, Amgen, MSD, Novartis; Advisory / Consultancy: MSD, Amgen, Novartis, Boehringer Ingelheim, AstraZeneca; Speaker Bureau / Expert testimony: Roche, AstraZeneca, Eisai, Amgen, MSD, Novartis; Travel / Accommodation / Expenses: Roche, MSD, Amgen, Novartis, Merck, Eisai, Taiho; Research grant / Funding (institution): MSD, Pfizer, Roche, AstraZeneca. K. Tanaka: Honoraria (self): Merck Serono, Bristol-Myers Squibb, Eisai, Ono Pharmaceutical, MSD, AstraZeneca; Advisory / Consultancy: Merck Serono, Bristol-Myers Squibb, Ono Pharmaceutical, MSD, Pfizer, Rakuten Medical, Celgene, Amgen; Research grant / Funding (institution): Bristol-Myers Squibb, Ono Pharmaceutical, MSD, Pfizer, Rakuten Medical, Novartis, Loxo, AstraZeneca, Rakuten Medical. R-L. Hong: Research grant / Funding (institution): MSD. W.Z. Wan Ishak: Honoraria (self): Eli Lilly Malaysia, Roche Malaysia, Pfizer Malaysia, MSD Ltd, Eisai Korea, Eisai Malaysia, Mundipharma, Merck Serono, Roche Myanmar; Advisory / Consultancy: Boehringer Ingelheim (M), Merck Serono (M), Roche (M), Eli Lilly (M), Amgen (M); Speaker Bureau / Expert testimony: Eli Lilly Inc; Research grant / Funding (self): Amgen Inc, MSD, Roche & Genetech, AstraZeneca; Travel / Accommodation / Expenses: Eisai (M), Eli Lilly (M), AstraZeneca (M), MSD Inc, Roche (M), Merck Serono (M), Mundipharma (M), Novartis (M), Pfizer (M), Amgen (M), Menarini (M). V. Sriuranpong: Honoraria (self): MSD; Advisory / Consultancy: MSD. S. Takahashi: Honoraria (self): Novartis, MDS, Eisai, Taiho, Chugai, Daiichi-Sankyo, Bayer, AstraZeneca; Research grant / Funding (self): MSD, Eisai, Taiho, Chugai, Daiichi-Sankyo, Bayer, AstraZeneca, Quintiles. N. Nohata: Shareholder / Stockholder / Stock options: Merck; Full / Part-time employment: MSD KK. A. Roy: Shareholder / Stockholder / Stock options, Full / Part-time employment: Merck & Co., Inc. B. Gumuscu: Shareholder / Stockholder / Stock options, Full / Part-time employment: Merck. R. Swaby: Shareholder / Stockholder / Stock options, Full / Part-time employment: Merck. M. Tahara: Honoraria (self): Merck Serono, Bristol-Myers Squibb, Eisai, Ono Pharmaceutical, MSD, AstraZeneca; Advisory / Consultancy: Merck Serono, Bristol-Myers Squibb, Ono Pharmaceutical, MSD, Pfizer, Rakuten Medical, Celgene, Amgen; Research grant / Funding (institution): Bristol-Myers Squibb, Ono Pharmaceutical, MSD, Pfizer, Rakuten Medical, Novartis, Loxo, AstraZeneca, Rakuten Medical. All other authors have declared no conflicts of interest.